Nexus between Fiscal Inclusion and Economic Growth of Nepal - Gajurel, Ram Prasad (Dristikon: A Multidisciplinary Journal, 2022)
This study is aimed to investigate the nexus between financial inclusion and economic growth of Nepal. This study employs descriptive as well as multiple regression model using the data over the period of mid-July 2014 to mid-July 2021 to examine the linkage between financial inclusion and economic growth of Nepal. The empirical results of the study reveal that there is strong association of financial inclusion with economic growth, however, there is no positive and robust impact of financial inclusion on economic growth of Nepal. In contrary, overall analysis of the study shows the strong evidence to support the view that financial inclusion is the backbone of the Nepali economy. This study covers only limited indicators of financial inclusion and limited periods of data which are not enough to evaluate the long-run relations of financial inclusion and growth of Nepal. This study suggests that policies promoting financial deepening and penetration and reforming the financial sectors to bond with the financial inclusion for economic growth of Nepal. In this study, we attempt to assess the significance of financial inclusion in economic growth so that piecemeal efforts can be made to combat Nepal's policy hitches and logjams.